Nuclear reactions in the Pd/PdO:D x and Ti/TiO 2:D x systems excited by ionizing radiation; Journal of Experimental and Theoretical Physics; Vol. 112, № 6 - Chernov I. P. Ivan Petrovich; Rusetskii A. S.; Krasnov D. N.; Larionov V. V. Vitaliy Vasilyevich; Lyakhov B. F.; Saunin E. I.; Tyurin Yu. I. Yuri Ivanovich; Cherdantsev Yu. P. (2011, 2011)
The yield of the products of nuclear reactions from deuterated palladium and titanium irradiated by an electron beam and X rays has been studied. Charged particles have been detected by CR-39 track detectors, which are not sensitive to electronic noise, electrons, and X-ray photons. To identify the type of particles and to estimate their energy, three detectors covered by aluminum and copper foils of various thicknesses have been used. It has been established with reliable statistics that 30-keV electrons and X rays initiate the synthesis of deuterons in the Pd/PdO:D x and Ti/TiO 2:D x systems with the yield of 3-MeV protons.